Analyze the Influential Factors on Successful Transformation of Traditional Energy Enterprises - Ying, Hao (Transactions on Economics, Business and Management Research, 2024)
At the beginning of the 21st century, the global energy landscape has experienced substantial transformation due to environmental and policy influences, leading Ørsted, a traditional energy company, to transition towards renewable energy within this context. This study report aims to investigate the factors influencing Ørsted's performance during the transition. This article gives a complete analysis of Ørsted's transition as a case study, utilizing Ørsted's yearly reports, the global energy landscape, and pertinent regulations for evaluation. The methodology incorporates theoretical principles of corporate social responsibility, business strategy, and corporate diversification. The principal factor stems from the corporation's increased commitment to social responsibility, and this report recommends that the company enhance its efforts in this area. The second rationale is strategic flexibility and innovation; this research advises the firm to bolster its strategic resilience and develop supply chain contracting capabilities. The third factor is industrial diversification. This research recommends that the firm concentrate on relevant and varied industries. This study provides a crucial reference for energy corporations and high-pollution businesses, while also providing as a theoretical framework and practical case support for the government and pertinent organizations in formulating energy policy and promoting renewable energy programs.